Oncoplastic surgery for Paget’s disease of the breast - Pelorca, Rafael José Fábio; de Oliveira-Junior, Idam; da Costa Vieira, René Aloisio (Frontiers in Oncology, 2023)
Introduction: Paget's disease of the breast (PDB) is a rare nipple entity associated with multifocality. Due to its location, resection of the entire nipple-areolar complex is necessary. Historically central quadrantectomy and mastectomy have the surgical treatments of choice. The feasibility of oncoplastic breast surgery (OBS) for PDB is unknown. Methods: This was a retrospective study performed in a Brazilian oncological hospital. We evaluated the factors related to the performance of OBS in PDB. In addition, the impact of OBS on local recurrence and survival was analysed. Comparisons were made between groups using the chi-square test, Mann‒Whitney U test, and Kaplan–Meier method. To assess the impact factor of the variables on the performance of OBS, logistic regression was performed. Results: Eighty-five patients were evaluated. OBS was performed in 69.4% (n=59), and of these, 16 (27.2%) were symmetrized with contralateral surgery. Mastectomy without reconstruction was performed in 28.3% of the patients. The primary procedure performed was mastectomy with reconstruction (n=38; 44.7%), and the preferential technique for immediate reconstruction was skin-sparing mastectomy with prosthesis; for late reconstruction, the preferred technique was using the latissimus dorsi. Breast conserving-surgery was performed in 27.0% (n=23), primarily using the plug-flap technique (OBS). Age was associated with the use of OBS; as patients aged 40-49 exhibited a higher rate of OBS (p = 0.002; odds ratio 3.22). OBS did not influence local recurrence (p=1.000), overall survival (p=0.185), or cancer-specific survival (p=0.418). Conclusion: OBS improves options related to surgical treatment in PDB without affecting local recurrence or survival rates.